Brain IGFBP-5 Modifies the Relation of Depressive Symptoms to Decline in Working Memory in Older Persons - Capuano, Ana W. (J Affect Disord, 2019)
BACKGROUND: Brain proteins, including Insulin-like Growth Factor Binding Protein 5 (IGFBP-5), have been associated with cognitive dysfunction in aging. Mechanisms linking depression with cognition are poorly understood. We hypothesize that the association of depressive symptoms with cognition is mediated or modified by brain proteins. METHODS: IGFBP-5, HSPB2, AK4, ITPK1 and PLXNB1 were measured in dorsolateral prefrontal cortex in 1057 deceased participants, who underwent annual assessments of depressive symptoms and cognition for a mean of 8.9 years. The average number of depressive symptoms per year before a dementia diagnosis was calculated for each person. RESULTS: A one standard deviation above the mean IGFBP-5 was associated with a 14% higher odds of having more depressive symptoms (p<0.031). Higher IGFBP-5 was associated with faster decline in global cognition (p<0.001) and five cognitive domains (p<0.008), controlling for depressive symptoms. IGFBP-5 moderated the association of depressive symptoms with decline in global cognition (p=0.045). IGFBP-5 mediated ten percent or less of the total effect of depressive symptoms on decline in global cognition and the cognitive domains (p>0.070). LIMITATIONS: Participants were volunteers and self-selection bias limits the generalizability of our findings. In addition, we used self-reported data on depressive symptoms. However, we also used data on depression medications as sensitivity analyses to confirm findings. CONCLUSIONS: In old age, brain IGFBP-5 is associated with depressive symptoms and cognition. The association of depressive symptoms with cognitive decline is conditional on IGFBP-5.